Il libro di Michea secondo la versione siriaca (Peshitto) - Pazzini, M.; Pierri, R. (Liber Annuus, 2005)
Abstract In this periodical, the Syriac versions of the texts of Amos, Jonah (LA 53) and Hosea (LA54) have already been published. The books of Joel and Obadiah have appeared on other publications. The project to publish the Twelve Minor Prophets has reached half way through with the publication of the book of Micah. The remaining books are already on their way and are expected to publish (complete) within next two years.